MENINGKATKAN SPIRITUALITAS REMAJA MELALUI PENDIDIKAN KELUARGA - Fuad Hilmi (Pergunu Jawa Barat, 2021)
Abstract The purpose of this research is to see how family education can improve youth spirituality. The method used is qualitative in which the data is in a natural setting with the intention of researching the phenomena that occur. Research based on theoretical studies on family education can improve the spirituality of adolescents keywords: education, youth, family